Natural disasters in the United States: making sense of risks and vulnerability - Rauscher, Natalie; Werner, Welf (Springer Nature Switzerland, 2025)
Chapter 1. Introduction -- Part I: Governance -- Chapter 2. Disaster Made Manifest: The Federal Role in U.S. Natural Disasters -- Chapter 3. Nature by Numbers: The National Flood Insurance Program -- Chapter 4. All of the Above: Energy, Environmental Politics, and U.S. Climate Change Policy since the 1970s Oil Crises -- Chapter 5. Letting Nature Do its Thing: Early Flood Control and Environmental Disaster along the Los Angeles River -- Part II: Representation and Perception -- Chapter 6. Hopeless Optimism: Framing Early 20th Century Earthquakes as News and History in the Making -- Chapter 7. Hurricanes and Theodicy in 20th and 21st Century American Protestantism -- Chapter 8. Through the Eyes of the White, Innocent Child: Whiteness, Vulnerability, and (Environmental) Crisis in Lauren Tarshi’s I Survived Series -- Chapter 9. Reporting Catastrophes: Mainstream Media and Vulnerability to Disasters in the U.S. -- Part III: Impact and Response -- Chapter 10. Multinational Insurers and Catastrophic Loss: Responses to the San Francisco Disaster of 1906 -- Chapter 11. Oil Ports and Hurricanes along the Texas Gulf Coast -- Chapter 12. ‘Becoming Green:’ Resilient and Green Building as Risk Mitigation in Atlanta, Georgia.